KESIAPAN PENDUDUK PEMUKIM DI DAERAH RAWAN LONGSOR KOTA SEMARANG - Suharini, Erni; Hariyanto, - (Forum Ilmu Sosial, 2008)
Every man needs a place to live in a safe and comfortable for the continuance of his life. Due tovarious factors, the human desire to live in areas prone to disasters such as landslides. Some of them donot know the danger they mengacam, there are some others who already know the risks that might occur,and then they make the steps antisipasinya. Those who live in landslide-prone areas have a differentmotivation. Motivation and the anticipation is what menajdi purpose of this research. Population researchis their (families) who live in areas prone to landslides in the city of Semarang. Identification of areasprone to landslides views of the topography / slope gradient and rock formation (formation Kalibiuk),which includes District Tembalang, Gunungpati, and Ngalian. Sample taken from the third kecamtan(purposively sampling) of 50 families. Data analyzed in quantitative descriptive. Results of research thatthey live in areas prone to landslides divided in two klas namely immigrants and native inhabitants. Themigrants generally live in housing built by developers who missal, their economic level is higher, nonagriculturallivelihoods. Instead of the native build their own home, a lower level of economic migrantson, livelihood of farmers or other informal sectors. Motivation migrants choose to stay here because ofthe consideration is close to the work, accessibility, high price. For the native land because of inheritanceand a source of livelihood here (rice field, moor). Both newcomers and the natives already know the riskof landslides. They differ only in mengapresiasi against landslides. Immigrants with anticipating technicalengineering building, such as strengthening the bones, make a levee, to reforestation. Erosion of the nativelook as natural occurrence, so no need to anticipate the technical engineering, they just do reforestation.One thing that has not been done by both migrants and their native population is on the socialization oftheir children Naka-how to save themselves in case landslides really happened.Keywords: Readiness of the population, the area prone to landslides, erosion